Evaluation of metformin in combination with rifampicin containing antituberculosis therapy in patients with new, smear-positive pulmonary tuberculosis (METRIF): study protocol for a randomised clinical trial. Issue 3 (1st March 2019) - Padmapriyadarsini, Chandrasekaran; Bhavani, Perumal K; Natrajan, Mohan; Ponnuraja, Chinnayan; Kumar, Hemanth; Gomathy, Sivaramakrishnan N; Guleria, Randeep; Jawahar, Shaheed M; Singh, Manjula; Balganesh, Tanjore; Swaminathan, Soumya
Abstract : Introduction: Shorter duration of treatment for the management of drug-susceptible pulmonary tuberculosis (TB) would be a significant improvement in the care of patients suffering from the disease. Besides newer drugs and regimens, other modalities like host-directed therapy are also being suggested to reach this goal. This study's objective is to assess the efficacy and safety of metformin-containing anti-TB treatment (ATT) regimen in comparison to the standard 6-month ATT regimen in the treatment of patients with newly diagnosed sputum smear-positive drug-sensitive pulmonary TB. Methods and analysis: We are conducting a multicentric, randomised open-label controlled clinical trial to achieve the study objective. The intervention group will receive isoniazid (H), rifampicin (R), ethambutol (E) and pyrazinamide (Z) along with 1000 mg of daily metformin (Met) for the first 2 months while the control group will receive only HRZE. After 2 months, both the groups will receive HRE daily for 4 months. The primary endpoint is time to sputum culture conversion. Secondary endpoints will include time to detection of Mycobacterium tuberculosis in sputum, pharmacokinetics and pharmacogenomics of study drugs, drug–drug interactions, safety and tolerability of the various combinations and measurement of autophagy and immune responses in the study participants. Ethics and dissemination: The ethics committee of the participating institutes have approved the study. Results from this trial will contribute to evidence towards constructing a shorter, effective and safe regimen for patients with TB. The results will be shared widely with the National Programme managers, policymakers and stakeholders through open access publications, dissemination meetings, conference abstracts and policy briefs. This is expected to provide a new standard of care for drug-sensitive patients with pulmonary TB who will not only reduce the number of clinic visits and lost to follow-up of patients from treatment but also reduce the burden on the healthcare system. Trial registration number: CTRI/2018/01/011176; Pre-results.